Integrity monitoring using multi-GNSS pseudorange observations in the urban environment combining ARAIM and 3D city models. Issue 1 (2nd January 2022) - El-Mowafy, Ahmed; Xu, Bing; Hsu, Li-Ta
ABSTRACT: Positioning integrity is essential in navigation. A novel approach is proposed for integrity monitoring that combines the Advanced Receiver Autonomous Integrity Monitoring (ARAIM) with Non-Line-of-Sight (NLOS) detection method using 3D city models to aid multi-constellation GNSS positioning in challenging urban scenarios. A demonstration of the proposed approach is performed with real data in an urban area in Hong Kong. The combined technique is tested via Single Point Positioning and simulated DGNSS positioning using a commercial-grade receiver. An improvement of fault detection capability and accordingly the obtained accuracy is shown when combining the two methods, compared to applying each method individually.